As trevas em Trevisan: por uma releitura do mito vampírico - Bordoni, Rita de Cássia (2011)
The main objective of this research is, by means of a comparative method, to do a critical analysis of O vampiro de Curitiba (The vampire from Curitiba) from Dalton Trevisan. This analysis will try to answer a core question: How can Dalton Trevisan rebuild one of the most ancient myths of the human culture the vampire one? To answer this problematic question, we have thought about three hypotheses: 1) The vampire myth is demystified in a parodical way, revealing his two faces: hero and victim; 2) The demystification is done through a sense of emptiness which can be observed in: the narrative, the hero and the narrator as well as in the discourse categories and all of this on the border between fiction and non-fiction; 3) The vampire myth demystification generates a social criticism effect in a time that life in the urban centers is in degeneration. The parody concept that we chose to guide the novel‟s analysis was taken from Bakhtin (1998) and Hutcheon (1985). These authors leaded us to a conclusion that Trevisan takes off the mythical vampire‟s aura. As he does this in the text, he transforms the myth in an unsacred one through resources like: love cannibalism and death, using the sex desire as his via cruces. In his trajectory in Curitiba, he allegorically configures the city as an urban Hades, in an attitude to criticize the values of a society in decomposition, the literary patterns in tension against the urban litter , which is characterized as a non-literary discourse